Swelling of self-adhesive resin cement increases long-term push-out bond strength of fiber post to dentin - Fabrício Mezzomo Collares; Vicente Castelo Branco Leitune; Carolina Rocha Augusto; Patrícia Franken; Susana Maria Werner Samuel (Universidade Estadual de Campinas, 2015)
Aim: To evaluate the long-term post push-out bond strength to dentin, water sorption, solubility and swelling of conventional and self-adhesive dual-cure resin cements. Methods: Forty-eight bovine roots were prepared for fiber post cementation with RelyX ARC and RelyX U100. According to resin cement and storage time (24 h and 6 months), 4 groups were assessed using the push-out test. Water sorption and solubility were performed according to ISO 4049:2009. The swelling coefficient was obtained using cement disks of each material immersed in distilled water until the swelling equilibrium was reached. The mass of dry and swelled polymer and solvent density were used to calculate the coefficient. Statistical data analysis was performed using Student's t-test for water sorption, solubility and swelling coefficient and the Kruskal-Wallis and Dunn multiple comparison tests for push-out analysis with a significance level of 0.05. Results: The immediate bond strength was not significantly different between RelyX ARC (3.09 MPa) and RelyX U100 (3.78 MPa) (p>0.05). RelyX U100 showed higher (p<0.05) bond strength after six months of storage (9.60 MPa) than RelyX ARC (6.65 MPa). The water sorption and solubility values were not significantly different (p>0.05) between groups. The swelling coefficient of the RelyX U100 group was significantly higher than that of the RelyX ARC group (p<0.05). Conclusions: RelyX U100 resin cement showed a higher swelling coefficient than RelyX ARC, and the longitudinal push-out bond strength increased after six months. Clinical significance: The clinical longevity of restorative treatment in root-filled teeth is dependent on the long-term properties and behavior of the cement used for post luting. Results of this study suggest that the selfadhesive resin cement may be a reliable alternative.